Use of Polynomial Regression to Investigate Biased Self-Perceptions and ADHD Symptoms in Young Adolescents. Issue 12 (October 2018) - Fefer, Sarah A.; Ogg, Julia A.; Dedrick, Robert F.
Objective: This study investigated biased self-perceptions of academic and social competence among young adolescents with a range of ADHD symptoms. The goal was to better understand how to measure agreement and disagreement between competence ratings from multiple informants.Method: The commonly used discrepancy methodology was used along with polynomial regression/response surface analyses to explore the relationship between biased self-perceptions and ADHD symptoms. Participants were 164 middle school students and their homeroom teachers. Students and teachers completed measures about academic and social competence, and teachers rated ADHD symptoms.Results: Discrepancy score and polynomial regression/response surface analyses both supported the relationship between student overestimation of competence and ADHD symptoms. Response surface analyses also suggest that some students with ADHD symptoms accurately perceive their impairments, particularly in the academic domain.Conclusion: Findings demonstrate the importance of using more advanced methods to understand the relationship between both accurate and discrepant perceptions of competence and ADHD symptoms.